UMPSA students Singgah Kopi enlivens 2023 Convocation Expo - Siti Nurfarmy, Ibrahim (UMPSA, 2023)
GAMBANG, 21 October 2023 – Singgah Kopi (literally translated as Coffee Stopover) is a coffee drink-based business run by student of the Faculty of Computing, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Nur Aysha Eliya Abdullah Sany with entrepreneurial mentor, lecturer of the Faculty of Electrical and Electronic Engineering Technology (FTKEE), Ts. Dr. Abdul Nasir Abd Ghafar.